Debt relief and changing governance structures in developing countries - Andreas Freytag; Gernot Pehnelt (European Centre for International Political Economy (ECIPE), 2006)
In this paper we empirically discuss the question whether or not debt relief in the past fifteen years has been economically rational. Analysing the determinants of debt relief our results suggest that governance quality did not play a role in the decision of creditor countries to forgive debt in the 1990s. Furthermore, even the actual debt burden of highly indebted poor countries had not been crucial for the decision whether or not debt forgiveness was granted. Rather, debt relief followed a strong path dependence: those countries whose debt had been forgiven in the first half of the 1990s were also granted debt forgiveness in the second half of this decade. However, this allocation pattern changed at the beginning of the 21st century, when the path dependence became less strong and at least some dimensions of governance quality have been taken into account by donor countries.
Keywords: O17; O19; O29; 330; debt relief; HIPC; development; governance; institutional quality; Schuldenerlass; Schuldenmanagement; Pfadabhängigkeit; Entwicklungsländer; Vierte Welt; Good Governance